1988
DOI: 10.1093/rheumatology/27.6.454
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Rheumatoid Arthritis in the Indian Population: A Prospective Study

Abstract: Evaluation of polyarthritis in 110 patients in civilian and armed force life revealed 89 with rheumatoid arthritis (RA). In the Indian population, RA seems milder and confined to the joints. A substantial number of male patients appeared to share features with spondylarthritis, often in HLA-B27 positive individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Family history 14% [23] found that out of 110 patients who came for evaluation of polyarthritis 89 had rheumatoid arthritis. Looking at the features of rheumatic disorders in a referral hospital in South India, rheumatoid arthritis was seen in elderly men and age of onset was 37.4 ± 9 years.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Family history 14% [23] found that out of 110 patients who came for evaluation of polyarthritis 89 had rheumatoid arthritis. Looking at the features of rheumatic disorders in a referral hospital in South India, rheumatoid arthritis was seen in elderly men and age of onset was 37.4 ± 9 years.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…The prevalence of osteoarthritis was 5.8(95% CI: 5.1-6.5) [4]. The prevalence of osteoarthritis was less in 30 years old than between older than 65 years old [23]. The female to male ratio was found to be 1.3:1.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Nine studies included data on comorbidities among RA patients (Table a). The comorbidities reported in more than one study included anemia, dyslipidemia and Sjögren's syndrome . The comorbidities reported among 30% or more of total RA patients included anemia, dyslipidemia, leukocytosis, thrombocytosis, tuberculosis and infections of unknown organisms (never isolated) …”
Section: Resultsmentioning
confidence: 99%
“…The percentages of patients diagnosed with extra‐articular manifestations that were not specified ranged from 15% to 61%. The specific extra‐articular manifestations reported among 20% or more of total RA patients included amyloid deposits, anxiety, subclinical atherosclerosis, malaise, neuropathy, osteoporosis and splenomegaly . Additionally, interstitial lung disease, small vessel vasculitis and uveitis were reported among juvenile RA patients…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation